Lonicericola fuyuanensis (Parabambusicolaceae) a new terrestrial pleosporalean ascomycete from Yunnan Province, China - Yasanthika, Erandi; Dissanayake, Lakmali S.; Wanasinghe, Dhanushka N.; Karunarathna, Samantha C.; Mortimer, Peter E.; Samarakoon, Binu C.; Monkai, Jutamart; Hyde, Kevin D. (Phytotaxa, 2020)
A new species of terrestrial ascomycetes belonging to the genus Lonicericola (Pleosporales, Dothideomycetes) found on dead branches of Caprifolioideae sp. in Yunnan Province, China is described and illustrated. A new classification is proposed to accommodate the new taxon based on the interpreted results from multigenic phylogenetic inference and micro morphological comparisons. The analysis of a combined SSU, LSU, ITS rDNA and tef1 dataset significantly supports both the shared monophyletic origin of Lonicericola in Parabambusicolaceae as well as L. fuyuanensis as a distinct new species. Comparisons of the distinct morphology of the new species L. fuyuanensis with the type species of the genus, L. hyaloseptispora, and other genera of the family Parabambusicolaceae are made.